Cover Feature: Circularly Polarized Absorption and Luminescence of Semiconductor Eu‐OCN Nanocrystals in the Blue Region of the Electromagnetic Spectrum (ChemPhysChem 17/2020). Issue 17 (3rd September 2020) - Hasegawa, Yasuchika; Koide, Katsumasa; Tsurui, Makoto; Kitagawa, Yuichi; Nakanishi, Takayuki; Doi, Yoshihiro; Hinatsu, Yukio; Fushimi, Koji
Abstract : The Cover Feature shows that the magnetic semiconductor Eu‐OCN provides polarized luminescence for photoscience and technology. More information can be found in the Communication by Yasuchika Hasegawa and co‐workers .